Pressure ulcer stages among bed-ridden patients in Ahmadu Bello University Teaching Hospital (ABUTH), Zaria- Nigeria - Ladan, Awwal M.; Garba, Saleh Ngaski; Sani, Dalhat Khalid; Sani, Hadiza Muhammad; Muhammed, Awwal Farooq (International Organization Of Scientific Research, 2014)
This study was carried out to assesspressure ulcer stages among bed-ridden patients in Medical, Neurosurgical and Orthopaedic wards inAhmadu Bello University Teaching Hospital (ABUTH) Shika-Zaria. The main aim of this study is to determine the prevalence as well as the stages of pressure ulcers among bed-ridden patients and to assess the Nurses’ awareness and application of the awareness in the stage-based treatment of pressure ulcer in ABUTH. The descriptive survey design was adopted and data was collected with the help of questionnaire and observation checklist. A convenient sampling method was used among the bed-ridden patients and a single-stage cluster method was used among the nurses in the three wards. The study sample consisted of 51 Nurses whom answered a pre-established Questionnaire and 129 bed-ridden patients whom were observed using Observational Checklist. The Major Findings were as follows: the cumulative point prevalence of Pressure ulcer was noted to be 18.6% which is significantly high; Pressure ulcer stages were observed to be highest for Stages III (37.5%), and Stage IV (33.3%) which are the advanced stages, and then low in Stage II (20.8%) and Stage I (8.3%). Furthermore, 96% of Nurses were observed to be aware of pressure ulcer stages and 82% apply their awareness in the stage-based treatment of pressure ulcer. In conclusion, there was a high prevalence of pressure ulcer among bed-ridden patients majority of which were the advanced stage of the condition. Therefore it is recommended that, use of a risk assessment tool such as theBraden Scale on admission will identify if the client has pressure ulcer or not, and if they do, at which stage, health care professionals should be more informed about secondary conditions that may occur in the course of patient’s stay in the hospital rather than emphasis only on primary condition that warranted admission, and patient’s relatives should be informed about the risk factors for the development of pressure ulcers since they are also fully involved in the care.